PENGARUH SELF-SERVICE TECHNOLOGY TERHADAP KEPUASAN PENUMPANG PADA MESIN SELF CHECK-IN DI BANDARA - Wahyu Firmansyah Padakari; Indratno, Diana Leli; R. Suprono Wahyujatmiko (ITB AAS Indonesia Surakarta, 2025)
The presence of Self Check-In service technology at international airports allows passengers to complete tasks without interacting with airport staff, which can improve the passenger experience, simplify operations, and increase passenger satisfaction. This study aims to evaluate the effect of self-service technology on passenger satisfaction at airports. Evaluation of effectiveness is needed to develop wider self-service technology at international airports. The study was conducted using a survey approach by distributing questionnaires both offline and online to 100 passengers who are currently or have used self-service technology at Yogyakarta International Airport (YIA). Data were analyzed using multiple linear regression analysis techniques. The results found that four dimensions of SST consisting of functionality, security, customization, and convenience have a significant effect on passenger satisfaction with self-check-in machine services at the airport. However, the enjoyment dimension does not have a significant effect on passenger satisfaction with self-check-in machine services at the airport. Some passengers are not familiar with new service technologies or prefer human assistance and are reluctant to use self-service technology. These results provide implications for YIA management to expand Self Service Technology at the airport gradually, conduct user training in the use of SST, and try hybrid services to ensure users can utilize it effectively. Keywords: Passenger Satisfaction, Self Service Technology, Self Check-In, Airport Management